The Welfare of Horses Competing in Three-Barrel Race Events Is Shown to Be Not Inhibited by Short Intervals between Starts - Helio C. Manso Filho; Keity L. G. Trindade; Carolina J. F. L. Silva; Raissa K. S. Cruz; César F. Vilela; Clarisse S. Coelho; José D. Ribeiro Filho; Helena E. C. C. C. Manso (Animals, 2024)
Equestrian sports require precise animal welfare and health evaluations. To test the hypothesis that horses maintain their welfare when subjected to two three-barrel (3TB) races with 2 min intervals, an experiment was designed to evaluate their surface temperature using infrared thermography (IRT) in regions of interest (barrel, flank, neck, jaw, corner of the mouth, and ocular caruncle) and also measure blood biomarkers (hemogram, total plasma protein, fibrinogen, urea, creatinine, GGT, CK, cortisol, IL-6, and IL-1β). Ten Quarter Horses were monitored through thermography (pre-race, +1, +4, and +24 h post-race) and blood sampling (pre-race, +1, +4, and +24 h post-race). ANOVA and Tukey test at 5% were used. IRT in six regions of interest (Left/Right—barrel, flank, neck muscles) increased at +, with no differences between values recorded at +1 and +4 when compared to those measured pre-race (p > 0.05). Plasma protein, RBC count, hemoglobin, hematocrit, WBC count, neutrophils, and lymphocytes (p < 0.05) increased immediately after the races, with recovery at +1 h. Other biomarkers did not change, including cortisol, IL-6, and IL-1β (p > 0.05). Results indicate that well-conditioned 3TB horses subjected to two races at short intervals do not show changes that could be related to impaired health or welfare.